Pengaruh Social Media Marketing Terhadap Customer Response Melalui Mediasi Brand Equity Pada Easybook - Famius, Mochammad Rayhan Shaquille; Giri, Refi Rifaldi Windya; Nurhazizah, Eva (eProceedings of Management, 2024)
The growing digitalization era strengthens the role of social media. Social media can now be used bybusinesses as a marketing strategy, not just for individual use. Various online travel agents inIndonesia, which have a service focus on bus ticket bookings, use Instagram social media as a means of marketing.its marketing. One of them is EasyBook. However, its implementation still gets a poor response from customers.from customers. This can be seen from the average number of engagements which indicates e-Wom and commitment on EasyBook's Instagram needs to be improved.on Instagram EasyBook needs to be improved. The purpose of this research is to find out how socialsocial media marketing affects customer response mediated by brand equity. Brand equity is seen as howconsumers perceive the value of the brand, in this case brand awareness and brand image. Quantitative methodused in this study with 385 respondents who have the criteria as Indonesians as EasyBook Instagram followers or individuals who have beenEasyBook Instagram followers or individuals who have seen EasyBook Instagram content and individuals who have used EasyBook.have used EasyBook. PLS - SEM was used as the data analysis technique. The results show thatsocial media marketing shapes brand equity before finally shaping customer response. Investment inbrand equity can increase customer response. Keywords-Social media marketing, brand equity, brand awareness, brand image, customer response, e-WOM,commitment.